PENGARUH PENERAPAN STRATEGI PEMBELAJARAN BERDIFERENSIASI PROSES TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMAN 3 SURABAYA - Rois Syahsiatus Shufiah; Siti Maizul Habibah; Oksiana Jatiningsih; Harmanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student learning interest is one of the factors that affect learning success. However, student interest in Pancasila Education subjects is still relatively low. This study aims to find out the effect of differentiated learning process strategies on students' learning interest at SMAN 3 Surabaya. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 68 students, with class XI-3 as the experimental class and XI-4 as the control class. The data collection technique used questionnaires and observations, while data analysis employed the Mann–Whitney U Test. The study results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, with a Mean Rank of 51.49 for the experimental class and 17.51 for the control class. These results indicate that the process-differentiated learning strategy affects students' learning interest in Pancasila Education at SMAN 3 Surabaya.